Designing digital sovereignty—an open federated EU web index for search - Renée Ridgway (communication +1, 2025)
Google crawls and indexes the web, providing hyperlinks and search results that are extremely profitable based on exchanges between users, advertisers and data brokers. Due to this “logic of accumulation” of data, the human expectation of sovereignty over one’s own life and authorship of personal experience is at stake (Zuboff 2019). Also of concern is state sovereignty and its ability to “reign in” Big Tech, which has been further undermined by lobbyists and regulatory bodies. Encompassing information and communication technologies, “digital sovereignty” is often viewed as a “third way,” committed to European norms and values instead of US or China’s business models. Applying document and critical discourse analysis, this article explores the “media and sovereignty” dilemma of search technologies structured by John Durham Peter’s “political-ethical urgencies” (2022): Section 230, conspiracy theory, a burning planet and surveillance capitalism. It then introduces a forthcoming EU funded Open Web Index (OWI) based on European values and jurisdiction. In tandem with its technical development, a Working Group Ethics (WGE) is generating an “ethics compass” including the value “Sovereignty/ Autonomy,” which is collectively discussed and then analysed by the author. Contributing to media and communication scholarship, the article proposes how this federated search index could embody digital sovereignty by instilling “digital communality” (Lehuedé 2024), thereby simultaneously challenging world capitalism’s accumulative and extractive ethos.
Keywords: alternative search; Designing digital sovereignty; digital communality; federated index